Attitudes Toward Organ, Tissue, and Vascularized Composite Allograft (VCA) Donation and Transplantation: A Survey of United States Military Veterans. Issue 5 (29th June 2020) - Ward, Stephanie; Boger, Matthew; Fleishman, Aaron; Shenkel, Jessica; Calvo, Amanda; Pomahac, Bohdan; Zwolak, Robert; Krishnan, Namrata; Rodrigue, James R.
Abstract : Background: There are 20 million living US armed forces veterans; however, the organ donation attitudes of veterans have not been examined. Methods: Over a 17-month period, a convenience sample of 1517 veterans in New England completed a survey to assess attitudes about organ, tissue, and vascularized composite allograft (VCA) donation. Results: Most veterans (96%) supported the donation of organs and tissue for transplantation, and 59% were registered as an organ and tissue donor. Being younger (adjusted odds ratio [aOR]: 0.96 0.970.98 ; P = 0.01), female (aOR: 1.06 1.462.03 ; P = 0.02), non-Hispanic white (aOR: 1.30 2.073.30 ; P = 0.01), Hispanic (aOR: 1.28 2.434.61 ; P = 0.01), and having more trust that the transplant process is fair and equal (aOR: 1.19 1.401.65 ; P = 0.01) were predictive of donor registration. Also, most veterans were willing to donate their face (57%), hands/arms (81%), legs (81%), penis (men: 61%), and uterus (women: 76%) at time of death; donation willingness was higher for upper and lower limbs than for face or genitourinary organs ( P < 0.001). Those unwilling to donate VCA organs expressed concerns about identity loss, psychological discomfort of self and others, body integrity, funeral presentation, and religious beliefs. Most (54%) felt that VCA donation should require permission of legal next-of-kin at the time of one's death, even if the decedent was a registered donor. Conclusions: There is a high level of support for organ, tissue, and VCA transplantation and donation among veterans, despite limited educational campaigns targeting this population. There is high potential among veterans to further increase donor registry enrollment and raise awareness about VCA benefits for severely injured service members.